Review of the development and application of aluminum alloys in the nuclear industry - Al Hasa Muhammad Husna; Adi Wisnu Ari; Djuhana Dede; Handoko Djati; Masrukan Masrukan; Alhasa Kemal Maulana; Sudjadi Usman (Reviews on Advanced Materials Science)
The necessity for lightweight components in the nuclear sector is driven by the requirement to minimize the total weight of the fuel. Aluminum alloys have emerged as the primary choice for incorporation into the nuclear fuel structure of research reactors, primarily serving as a cladding material for the containment of uranium fuel. Their utilization is driven by their ability to fulfill the prerequisite of having a lower relative density than other metals, thereby contributing to a reduction in the total weight of the fuel. Furthermore, they demonstrate superior mechanical properties, thermal characteristics, and corrosion resistance. Aluminum alloys, such as AlFeNi and Al 6061 (AlMgSi), showcase commendable mechanical attributes, thermal behavior, and stability, being amenable to strengthening through specific heat treatments, consequently demonstrating favorable performance as cladding materials in nuclear applications and thereby extending the lifespan of the fuel. Additionally, aluminum alloys have a very small neutron absorption cross-section, so neutron absorption is relatively low, and more neutrons will be transmitted to the fuel. This study presents a literature review on aluminum alloys from various experiments for use in the nuclear industry, detailing their production methods, and elucidating their influence on mechanical properties, thermal behavior, and stability, focusing on recent research findings. Furthermore, this review outlines existing challenges and offers a comprehensive roadmap for prospective research. The strength of the cladding material should be increased to encase high-density fuel, which will impact the fuel’s lifespan, thereby making it more economically efficient.